Experiences of Stutterer Nurses in the Provision of Nursing Care in Pakistan - Ullah, Rizwan; Ali Shah, Bakhtyar (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2023)
Introduction: "Stuttering" is a speech disorder that disrupts the flow of communication, often manifested through involuntary pauses, repetitions, or prolongations. These interruptions can cause significant anxiety, depression, and embarrassment for the individual. This study examined the lived experiences of nurses who stutter while caring for patients in a clinical setting. Method: Using a purposive sampling technique, a qualitative descriptive phenomenology design was employed to recruit nine stutter nurses (six males and three females). Individual, face-to-face, semi-structured interviews were conducted and analyzed through thematic analysis. Results: The analysis of the participants' narratives revealed three major themes, each with associated sub-themes. The first theme addresses the triggers of stuttering, with stress identified as the most prominent factor. The second theme explores the impact and effects of stuttering within the nursing profession, including sub-themes such as The predominantly negative impact on self-esteem and the minimal effect on clinical care, The lack of effect on relationships with colleagues, and The significant impact on relationships with patients. The third theme focuses on the management strategies employed by nurses who stutter, with sub-themes related to techniques used to mitigate stuttering in clinical settings. Conclusions: Stuttering does not inherently affect a nurse's ability to deliver compassionate and effective care. By using strategies to manage their stuttering and seeking support from colleagues and supervisors, a nurse who stutters can communicate effectively with patients and thrive in their clinical practice.